Flocculation Performance and Kinetics of Magnetic Polyacrylamide Microsphere under Different Magnetic Field Strengths - Wentian Yu; Chen Wang; Gengliang Wang; Qing Feng (Journal of Chemistry)
In this study, the flocculation performance and kinetics of magnetic cationic polyacrylamide (MCPAM) microspheres, compared with cationic polyacrylamide (CPAM), were systematically investigated under different magnetic field strengths. Flocculation performance was observed by jar test experiment. The density of flocs was estimated by the determination of floc settlement velocity and image analysis. The frequency distribution of floc size was measured with a Malvern Mastersizer instrument. When the diatomite suspension was treated by MCPAM and CPAM, the residual diatomite turbidity was 16.28 NTU and 244.13 NTU, respectively. The maximum turbidity removal efficiency of MCPAM was about 99.65% under 1000 Gauss magnetic field, which was higher than that (94.75%) of CPAM. The synergy of gravitational and magnetic fields for MCPAM promoted the formation of larger flocs with higher growth rates compared with CPAM. The effective density range of flocs in the MCPAM flocculation was increased to 10–252 kg m−3. The kinetic constants were calculated by monitoring the frequency of floc collisions. The increase of kinetic constant (k) to 25.81 × 10−11 s−1 suggested that interaction of contact and collision between magnetic flocs was sufficient. According to the evolution of the size and density of flocs under the synergy of gravitational and magnetic fields, the magnetic flocculation rate equation dN/dt=−1/9μρ−ρlg+ρkmHdH/dXai2−aj2−ai2e9μt/2ai2ρ+aj2e9μt/2aj2ρai+aj2 was derived. The study of magnetic flocculation kinetics can provide theoretical support for magnetic flocculation and is critical for the analysis of solid-liquid separation processes.